이수종 구조용집성재의 전단접착력 및 접착내구성 평가 - 심상로; Sang Ro Shim; 여환명; Hwan Myeong Yeo; 심국보; Kug Bo Shim (목재공학, 2005)
This study was carried out to evaluate the shear bond strength and adhesive bond durability of structural glued laminated timber (glulam) manufactured with mixed species lumber of Korean red pine, Korean pine and Japanese larch, using resorcinol adhesive and water-based polymeric-isocyanate adhesive (WPI). Each board used as a glulam lamina was graded by visual inspection. The visual lumber grade of the all species was very low due to the large size and number of knots and the steep slope of grain. In view of the results, appropriate pruning, sawing and drying processes might be needed to produce high grade lamina lumber with small knot size and drying defect free. Shear bond strength of every tested glulam specimen ranged between 7.9 and $9.9N/mm^2$, and much higher than the Korean Standard (KS) for glulam shear bond strength, $7.1N/mm^2$. There was not much shear bond strength difference between wood/resorcinol and wood/WPI. The resorcinol adhesive bond durability exceeded KS requirements. However, delamination on the end-grain surfaces of WPI glulam submerged in both room temperature and boiling water severely occurred, and its durability did not meet KS requirements. Further investigations may be required, and special care should be taken, to ensure long service life of WPI glulam used for exterior application. Results of this study are expected to be useful for improvement of mechanical properties and structural performance of mixed species glulam. 본 연구에서는 국산재의 구조용집성재 라미나로의 이용을 위해 국산 소나무, 잣나무와 낙엽송 공시판재에 대하여 육안품질을 평가한 후, 레조르시놀수지와 수성고분자 이소시아네이트수지 접착제로 접착하여 제조한 단일수종 및 이수종 혼합 구조용집성재의 전단접착력과 접착내구성을 평가하였다. 국산재의 구조용집성재 라미나로의 이용을 위해 공시판재에 대한 육안품질등급 구분을 실시한 결과, 소나무, 잣나무 및 낙엽송의 육안품질 종합등급은 재내 잔존하는 크고 많은 옹이와 함께 큰 목리경사각으로 인해 낮은 등급의 판재 비율이 상당히 높게 나타났다. 좀더 높은 등급의 판재를 생산하기 위하여 가지치기 등의 육림작업과 할렬 및 비틀림 등의 결함을 줄이기 위한 제재 및 건조공정 개발이 필요할 것으로 판단되었다. 레조르시놀 수지 접착제와 수성고분자 이소시아네이트 수지 접착제로 제조된 단일수종 및 이수종 혼합 집성재의 전단강도는 $7.9{\sim}9.9N/mm^2$ ($80.9{\sim}101.3kgf/cm^2$) 범위 내에 있어 A수종군의 KS규격 전단강도인 $7.1N/mm^2$ ($72kgf/cm^2$)을 훨씬 상회하는 우수한 접착력을 나타내어 사용된 두 접착제 모두 강도적인 문제는 발생치 않을 것으로 판단되었다. 또한 레조르시놀 수지 접착제를 사용하여 제조한 단일수종 집성재와 이수종 혼합집성재의 침지 및 삶음박리시험 결과 모든 시험편이 KS 기준을 상회하여 접착내구성에도 역시 문제가 없음을 보여주었다. 그러나 수성고분자 이소시아네이트 수지 접착제로 제조된 단일수종 및 이수종 혼합 집성재의 침지와 삶음 박리율은 매우 높아 이 접착제를 구조용집성재용 접착제로 사용할 경우는 집성재의 사용환경을 신중히 고려하여야 할 필요가 있었다. 본 연구결과는 국산 소나무, 잣나무 및 낙엽송 단일수종 구조용집성재와 이수종 혼합집성재 제조를 위한 기초자료 제공 및 품질 향상에 사용될 수 있으리라 기대된다.